FATHER PARTICIPATION AND ITS EFFECT ON MOTOR DEVELOPMENT OF 4 YEARS-OLD CHILDREN IN KINDERGARTEN - Mufida Annisa Rahmawati; Fitri Meilani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: From 2-5 years old is called the preschool years, one of child development in this main area is sensory and motor development. Father’s figure has become an important resource for children under 5 year developing self regulation skills. Aims: This study aims to know father participation of motor development for children under 5 year. Method: This is a research survey using cross sectional analysis (range spearman) with 77 respondent taken from total sampling technique. Data collection was done in one month (April-May, 2013) using questionnaires and DDST (Denver Development Screening Test). Result: The research indicates that 82% children have normal motor development with father who participates in caring process,, whilst 50% children without father participation have an incomplete motor development. There are positive correlation between father participation and motor development for children under 5 years Conclusion: Fathers participation is necessary for development of child’s motor..